Quality of Life in Children with Acyanotic Congenital Heart Disease in Dr. Soetomo General Hospital, Surabaya, Indonesia - Salsabila Fabianca Alsaid; Taufiq Hidayat; Heroe Soebroto (Universitas Airlangga, 2022)
Abstract: Acyanotic congenital heart disease is a disease that affects the patient physically and psychologically result in the patient not being able to carry out his life normally. As a result, patients will feel lonely, rejected, and isolated from society which makes social integration more difficult. The picture of quality of life in acyanotic CHD patients can be used as a therapeutic evaluation material to improve quality of life. Material and Methods: This study used descriptive analytic method with total sampling. The variable studied was quality of life using Pedsql Inventory 3.0 Cardiac Module questionnaire to the patients aged 2-18 years who were treated at Dr. Soetomo General Hospital Surabaya in 2019—2020. Results: 74 Acyanotic CHD patients (left to right shunt) obtained an average quality of life of 73.89 ± 9.79 with low-value aspects, namely Heart Problems and Therapy I (72.92 ± 18.20), Cognitive (59.53 ± 18.40), and Communication (71.40 ± 24.21). There was a significant difference in the type of combination diagnosis compared with other types with a significance of 0.014 (p <0.05). Conclusion: Aspects that have a negative impact on the patient's quality of life are Heart Problems and Therapy I, Cognitive, and Communication. The Combination type is a diagnosis with the lowest quality of life compared to other types. Keywords: Acyanotic CHD, PedsQL, Quality of life